Decomposing the Intraurban Malnutrition Gap Between Poor and Non-poor Children in Colombia (2022)
In Colombia, although it can be said that, on average children living in urban areas have better quality of life than their rural peers, it is also true that within cities, there are high levels of socioeconomic inequality. Our objective is to identify the contribution of the factors that explain the gap in stunting and excess weight between poor and non-poor children under 5 years of age in urban areas of Colombia. We use data from the 2015 National Nutritional Status Survey, and two nonlinear decomposition techniques based on the classical decomposition method developed by Blinder-Oaxaca. With a sample of 6877 observations, the results show that the intraurban gap of stunting between poor and non-poor children in urban areas is 4.8 percentage points. Its main determinants are the mother’s educational level (46.5%), afliation to the health system by the mother (19.4%), and assisted delivery in a medical institution (16.6%). For excess weight, the gap is−2.1 percentage points, and its main determinants are the mother’s educational level (39.2%) and birth attended by a physician (21.8%). This study suggests the coexistence of a double burden of malnutrition (DBM) in children under 5 years of age living in urban areas of Colombia. Stunting is associated with low-income levels while excess weight is associated with higher income levels. The identifcation of the main determinants of DBM and its relative importance, constitutes a contribution for public policy makers aimed at reducing socioeconomic gaps.